Damage assessment of stiffened steel plate shear walls with different configurations under far-fault and near-fault ground motions. (January 2023) - Labibzadeh, Mojtaba; Khayat, Majid
Abstract: Preventing damages and reducing the consequences of natural disasters such as earthquakes are nowadays considered as the most important considerations in improving the existing structures or designing new ones. A steel plate shear wall (SPSW) is one of the systems that resist lateral loads. Despite its significant benefits such as load capacity, plasticity, and high energy absorption capacity, the SPSW has a serious weakness: early buckling of infill plates under lateral loads. To solve this problem, some stiffeners with various distributions and geometries are used in the SPSWs. Adding these stiffeners brings about some changes in the seismic behavior (such as the seismic damages) of the structure. Therefore, in this study, we investigated the effects of various configurations of stiffeners in the shear walls on the damage level of the structures (5, 10, 15, and 20 floors) under earthquake excitations. The shear walls are either with openings (due to their implementation aspects and easy application) or without openings. Thirty-three earthquake excitations were applied (both far-field and near-field earthquakes) on the structures. Also, a non-linear dynamic analysis was performed to calculate the damages according to the three damage indexes of Park-Ang, Iemura-Mikami, and relative displacement. First, the structures were designed and modeled by the finite element software. Then, according to the definition of damage indices, the damage and performance level of the structures under earthquake records were studied and evaluated. The obtained results were presented in two separate parts. In the first part, due to the importance of model verification, the results of the study were compared with the results of the experimental models of the SPSWs with different stiffener configurations. In the second part, the effects of various configurations of stiffeners on damage indices of the SPSW with and without openings were evaluated. Based on the obtained results, the configurations of steel shear walls including the distribution of stiffeners and openings were found to have a significant effect on the amount of damage caused by seismic excitations. This effect depends on various factors for which the details are presented in this study. Highlights: Damage assessment of the steel plate shear walls with and without the stiffeners Studying the effect of different configurations of the shear wall on damage indices Studying the effect of type of earthquake excitations (far-fault and near-fault ground motions) on damage indices Studying the effect of the opening of shear wall on damage indices